2023
DOI: 10.1097/md.0000000000033339
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the efficacy of intra-articular injection of different drugs in the treatment of mild to moderate knee osteoarthritis: A network meta-analysis

Abstract: Background: Knee osteoarthritis (KOA) has a high clinical prevalence and frequently interferes with patients normal lives. In KOA patients, evidence suggests that intra-articular (IA) injection improves joint function and decreases discomfort. Several IA injection treatments are used in daily practice to improve symptomatic control of knee osteoarthritis, but their efficacy is frequently disputed. Methods: This network meta-analysis compares the efficacy of different IA inj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Our findings also addressed, a higher reduction was documented as regards pain score and analgesic requirement in ozone group at short-term (1-month post injection), but at long term (3 and 6-months post injection) there was higher reduction in pain score and analgesic requirement in PRGF group. Supporting out findings, Raeissadat et al [3] and Xue et al [19] showed that PRGF injections have the best longterm outcome in terms of pain reduction, and consequently reduction in analgesic requirement compared to other treatment modalities including ozone injection. Also, Gaballa et al [20] and Duymus et al [21] addressed, PRP injection have better long-term outcome in terms of pain reduction, and consequently reduction in analgesic requirement compared to ozone injection.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Our findings also addressed, a higher reduction was documented as regards pain score and analgesic requirement in ozone group at short-term (1-month post injection), but at long term (3 and 6-months post injection) there was higher reduction in pain score and analgesic requirement in PRGF group. Supporting out findings, Raeissadat et al [3] and Xue et al [19] showed that PRGF injections have the best longterm outcome in terms of pain reduction, and consequently reduction in analgesic requirement compared to other treatment modalities including ozone injection. Also, Gaballa et al [20] and Duymus et al [21] addressed, PRP injection have better long-term outcome in terms of pain reduction, and consequently reduction in analgesic requirement compared to ozone injection.…”
Section: Discussionmentioning
confidence: 69%
“…Indicating better long-term outcome in PRGF group. This was supported by the meta-analysis by Xue et al [19] addressing, PRGF was associated with better prolonged outcomes as opposed to ozone treatment. After one month knee flexion exhibited significantly greater values within O group in comparison with P group (P=0.004) (improvement in ROM).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Methotrexate and ozone therapy are also described in the literature [ 40 ]. Hyaluronic acid injections (viscosupplementation) and platelet-rich plasma injections are being evaluated [ 41 ]. Intra-articular injections may be guided by landmarks, fluoroscopy, or ultrasound, with excellent evidence available for ultrasound-guided procedures.…”
Section: Reviewmentioning
confidence: 99%
“…Clinical treatment involves a step-wise strategy, and systematic conservative treatment is usually adopted for early- and middle-stage OA. The non-surgical treatments for OA now mainly include nonsteroidal anti-inflammatory drugs (NSAIDs), intra-articular injections of platelet-rich plasma (PRP), hyaluronic acid (HA), steroids, and mesenchymal stem cells (MSCs) 3 . Among them, HA is a high-molecular-weight biological polysaccharide, which can play a role in chondroprotection both in vivo and in vitro .…”
mentioning
confidence: 99%